2015
DOI: 10.1017/s0144686x15000422
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with social care services among South Asian and White British older people: the need to understand the system

Abstract: National surveys show that people from minority ethnic groups tend to be less satisfied with social care services compared with the white population, but do not show why. Research indicates that barriers to accessing services include lack of information, perceptions of cultural inappropriateness and normative expectations of care. Less research has examined the experience of minority ethnic service users after they access services. This study conducted in-depth interviews with 82 South Asian and White British … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…The women wanted a confidential, trusting, and dignified relationship with key gatekeepers such as their GP, but due to GP workloads and appointment systems, this was not always possible. These negative experiences of formal care might be one reason why Willis, Khambhaita, Pathak and Evandrou found that surveys consistently demonstrate how people from BAME groups are less satisfied with social services compared with others. Other research also suggests that older people, in general, want to be actively listened to, with services tailored to their needs, and that professionals should give “good care” that respects diversity and individual choice…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The women wanted a confidential, trusting, and dignified relationship with key gatekeepers such as their GP, but due to GP workloads and appointment systems, this was not always possible. These negative experiences of formal care might be one reason why Willis, Khambhaita, Pathak and Evandrou found that surveys consistently demonstrate how people from BAME groups are less satisfied with social services compared with others. Other research also suggests that older people, in general, want to be actively listened to, with services tailored to their needs, and that professionals should give “good care” that respects diversity and individual choice…”
Section: Discussionmentioning
confidence: 99%
“…Findings from these surveys consistently demonstrate how people from BAME groups are less satisfied with social services, compared with others (eg, The NHS Health and Social Care Centre). Willis, Khambhaita, Pathak, and Evandrou further emphasise that this is an important finding, as services should be appropriate for all needs. Research suggests that those who are satisfied with service provision are more likely to comply and seek support for future needs …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The participants were service users, informal carers, and social care practitioners. The aim of the interviews was to understand reasons for satisfaction with social care, and to examine how ethnicity, language, religion, and culture might have a bearing (Willis et al 2015). Ethical approval was obtained from the Social Care Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6] This may be due to lack of awareness of dementia in minority ethnic groups, with memory problems being viewed as a normal part of ageing. 7,8 Willis et al, 9 Parveen et al, 10 and Greenwood et al 11 report a number of perceived barriers for minority ethnic communities accessing services, such as navigating complex social care pathways, language barriers, cultural stigma, lack of community-based services, concerns about cultural and religious appropriateness of services, and culturally preferred coping strategies.…”
Section: Introductionmentioning
confidence: 99%